HF-free synthesis of Si/C yolk/shell anodes for lithium-ion batteries. Issue 6 (22nd January 2018) - Huang, Xingkang; Sui, Xiaoyu; Yang, Hannah; Ren, Ren; Wu, Yingpeng; Guo, Xiaoru; Chen, Junhong
Abstract : A HF-free approach was designed for synthesizing a Si@C@void@C anode for high-performance Li-ion batteries. Abstract : A HF-free approach was designed for synthesizing Si@C@void@C as an anode for Li-ion batteries, in which two layers of polymers with various C yield upon calcination were chemically grown on Si particles, followed by carbonization to remove the inner polymer, leaving void spaces and coating a thin inner layer of C, while forming an exterior C shell from the outer polymer layer.